An Overview of the CRISPR-Based Genomic- and Epigenome-Editing System: Function, Applications, and Challenges - Saeed Bozorg Qomi; Amir Asghari; Majid Mojarrad (Advanced Biomedical Research, 2019)
Developing a new strategy for an efficient targeted genome editing has always been a great perspective in biology. Although different approaches have been suggested in the last three decades, each one is confronting with limitations. CRISPR-Cas complex is a bacterial-derived system which made a breakthrough in the area of genome editing. This paper presents a brief history of CRISPR genome editing and discusses thoroughly how it works in bacteria and mammalians. At the end, some applications and challenges of this growing research area are also reviewed. In addition to moving the boundaries of genetics, CRISPR-Cas can also provide the ground for fundamental advances in other fields of biological sciences.